Self-Control as a Protective Factor Against Self-Harm Behavior in Adolescents - Dewi, Putu Siska; Sulistiowati, Ni Made Dian; Sani Utami, Putu Ayu; Swedarma, Kadek Eka (Universitas Muhammadiyah Semarang, 2025)
The inability of adolescents to complete their development and the lack of effective coping strategies can cause adolescents to engage in self-harm behavior. If left unchecked, this action can have a negative impact, so self-control is needed in the form of self-control. The purpose of this study was to determine the relationship between self-control and self-harm behavior in adolescents. The type of research used is descriptive correlation with a cross-sectional design. A total of 335 respondents were selected based on the proportionate stratified random sampling technique from a total of students in grades VII, VIII, and IX spread across 30 classes. Data collection used the Brief Self-Control Scale questionnaire and the Self-Injury Behavior Tendency questionnaire directly and was analyzed using the Spearman rank test. The results of the study showed that there was a relationship between self-control and self-harm behavior (p-value = 0.000; r = -0.569), which means that self-control and self-harm behavior have a strong relationship with a negative (opposite) relationship direction. The higher the self-control, the lower the self-harm behavior that is carried out. Self-control in adolescents greatly influences how adolescents behave in the situations they face, so it is important for adolescents to have high self-control in order to prevent self-harming behavior.